Sultan Abdurrahman Khalifatul Mu’minin Sayyidul Imam : Perannya terhadap Kesultanan Palembang Darussalam - Ade Tunggal Bahial Halim; Mohammad Syawaluddin; Padila (Tanjak: Sejarah dan Peradaban Islam, 2024)
This research discusses the role of Kimas Hindi or Sultan Abdurrahman Khalifatul Mu’minin Sayyidul Imam in establishing the Palembang Sultanate which began because of the feud between the Palembang Kingdom and the Mataram Sultanate, which made Kimas Hindi as the ruler of the Palembang Kingdom desperate to break free from Mataram’s power, then deliberately made Palembang a sultanate so that its position became equal to Mataram. The framework of this subject matter, among others: (1) How is the socio-cultural description of the Palembang Sultanate? (2) How is the role of Sultan Abdurahman Khalifatul Mu’minim Sayyidul Imam in establishing the Palembang Sultanate and his role in government. This research uses qualitative data. While the data sources in this study come from primary data and secondary data. Then data collection uses interpretation or historical analysis, as well as historiography. From the results of the research, it can be seen that the socio-cultural life in the Palembang Sultanate is very From the results of the research, it can be seen that the socio-cultural life in the Palembang Sultanate was very concerned so as not to conflict with Islamic law. The culture that had existed before the Palembang Sultanate was improved so as not to conflict with the Sharia. The socio-cultural life that spread in various aspects of life in the Palembang Sultanate included clothing or clothing, arts, titles (status), customary law, language, and so on. While the formation of the Palembang Sultanate was the role of Sultan Abdurrahman Khalifatul Mu’minin Sayyidul Imam after breaking away from the power of the Mataram Sultanate and making the Palembang Kingdom an independent state by changing it to the Palembang Sultanate so that the position of Palembang and Mataram became equal. The role of Sultan Abdurrahman in his government included moving the center of government which was originally in Kuto Gawang then transferred to Beringin Janggut, re-establishing relations with the Dutch in trade matters, spreading Islam, and establishing relations with other kingdoms.